2000
DOI: 10.1086/315551
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Diphtheria

Abstract: Diphtheria is an acute, communicable disease caused by Corynebacterium diphtheriae. The disease is generally characterized by local growth of the bacterium in the pharynx with pseudomembrane formation or, less commonly, in the stomach or lungs; systemic dissemination of toxin then invokes lesions in distant organs. Acute disease of the upper respiratory tract usually involves one or more of the following: tonsillar zones, larynx, soft palate, uvula, and nasal cavities. A recent epidemic in Russia emphasized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
144
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(159 citation statements)
references
References 13 publications
1
144
1
7
Order By: Relevance
“…diphtheriae is the classical aetiological agent of diphtheria (Hadfield et al, 2000;Burkovski, 2013a, b), a localized toxaemic infection of respiratory tract that can be fatal. Moreover, it can cause skin ulcers (cutaneous diphtheria) as well as systemic infections such as endocarditis, meningitis, pneumonia and others (Murphy, 1996;Burkovski, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…diphtheriae is the classical aetiological agent of diphtheria (Hadfield et al, 2000;Burkovski, 2013a, b), a localized toxaemic infection of respiratory tract that can be fatal. Moreover, it can cause skin ulcers (cutaneous diphtheria) as well as systemic infections such as endocarditis, meningitis, pneumonia and others (Murphy, 1996;Burkovski, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Although diphtheria has now been virtually eliminated in the industrialized world, rare outbreaks still occur worldwide (1,2). Corynebacterium diphtheriae was shown to be the causative agent of diphtheria by Loeffler in 1885 (3), and Roux and Yersin showed that an extracellular toxin, diphtheria toxin (DT) secreted by C. diphtheriae is responsible for toxicity (4).…”
mentioning
confidence: 99%
“…When Corynebacterium diphtheriae infects humans, it generally has an incubation period of 2 to 5 days [129]. It typically infects anterior nasal, tonsillar and pharyngeal, laryngeal, cutaneous, ocular and genital areas, which means that it can grow in any mucous membrane and in the skin [52,82]. As well as destroying local cells at infection sites, the diphtheria toxin can also enter the bloodstream and reach out to organ cells that have its receptor, typically heart and nerve cells.…”
Section: How Corynebacterium Diphtheriae Causes Illnessmentioning
confidence: 99%